Zivitofsky and the Politics of Passports. (2015) - Torpey, John
Abstract : In Zivotofsky v. Kerry, the Supreme Court addressed the constitutionality of a 2002 law, Section 214(d) of the Foreign Relations Authorization Act for Fiscal Year 2003, which required consular officials to mark the word "Israel" as the birthplace of U.S. citizens who were born in Jerusalem if they requested that designation. The U.S. State Department refused to comply, pursuant to a policy of neutrality by the executive branch of the U.S. government concerning sovereignty over the much-contested city. The parents of a boy born in Jerusalem sued in federal court to see the law enforced. In its decision, the court found that Section 214(d) was an unconstitutional usurpation by Congress of the President's exclusive authority to recognize foreign governments. The policy of official U.S. neutrality in regard to sovereignty over Jerusalem was upheld.